EVALUASI KUALITAS SISTEM JURNAL ELEKTRONIK BERBASIS OPEN JOURNAL SYSTEM (OJS) MENGGUNAKAN ISO/IEC 25010 - Murdiani, Deni; Umar, Rusydi (Direktorat Repositori, Multimedia, dan Penerbitan Ilmiah - Badan Riset dan Inovasi Nasional (BRIN Publishing), 2020)
The electronic journal system based on the Open Journal System (OJS) developed by KKP is a system used for the management of publishing a scientific journal. With this system the journal management process becomes easier, faster and also transparent. To see whether the system that has been designed is in accordance with the wishes of the user and how much the level of satisfaction, it is necessary to evaluate the system that has been running. The evaluation carried out in this study uses 4 characteristics found in ISO / IE 25010. The results are in testing functional suitability characteristics, the system meets the standard because the main function of the system built runs smoothly because it has a value of X close to 1 which is 0.9 . In testing the performance efficiency characteristics have met the standard because the average time required to load the page for 3.7 seconds. On the usability characteristics, 76% of respondents stated that the MAARIF journal management system electronically was quite useful and satisfied for the manager and active reader of MAARIF Journal. Meanwhile, the security characteristics test shows that MAARIF electronic journal management system has level 2 or medium level security.